Penggunaan Software HEC-RAS Pada Pemodelan Angkutan Sedimen Dasar di Saluran Primer D.I. Maloso - Abdi Manaf; Imam Rohani; Amalia Nurdin; Savni Alkayatni (Jurnal Karajata Engineering, 2025)
Despite being equipped with mud pockets, the Sekka-sekka Dam still requires routine maintenance due to sediment accumulation in the Primary Canal. Sediment modelling has become an effective approach to identify areas with high sedimentation to make maintenance more focused and efficient. This research aims to determine the sedimentation patterns that occur, model the transport of bed sediment, and analyse the magnitude of bed sediment transport in the D.I Maloso primary canal using Hec-Ras software. The analysis was conducted using a Quasy-Unsteady Flow approach, with input comprising cross-sectional data of the canal, a flow discharge of 33.81 m3/s, and the characteristics of the bed sediment. The simulation results indicate the presence of sediment transport along the canal, with a dominance of fine sand and medium sand fractions. The total sediment transport over one month in the upstream reached 14,551 kg/month with a sediment thickness of 0.00227 m, in the midstream 35,351 kg/month (0.00551 m), and downstream 23,791 kg/month (0.00371 m). The shear stress values were 0.0080 Pa, 0.0078 Pa, and 0.0076 Pa respectively, with a fall velocity of 0.26 m/s upstream, and 0.2 m/s in the midstream and downstream. The average sediment concentration over three months was 0.3 mg/l, with the highest concentration recorded downstream at 4.8 mg/l. This modelling demonstrates the distribution of transported sediment in the canal, with the highest accumulation downstream due to the decrease in flow velocity and shear stress.